2015
DOI: 10.1038/nature14139
|View full text |Cite
|
Sign up to set email alerts
|

Vertically transmitted faecal IgA levels determine extra-chromosomal phenotypic variation

Abstract: SummaryThe proliferation of genetically modified mouse models has exposed phenotypic variation between investigators and institutions that has been challenging to control1-5. In many cases, the microbiota is the presumed culprit of the variation. Current solutions to account for phenotypic variability include littermate and maternal controls or defined microbial consortia in gnotobiotic mice6,7. In conventionally raised mice, the microbiome is transmitted from the dam2,8,9. Here we show that microbially–driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
174
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(191 citation statements)
references
References 35 publications
8
174
1
2
Order By: Relevance
“…Our results highlight observations that some of the observed phenotypic variation in animal studies is, in part, owing to variations in the microbiota. For example, it was recently shown that differences in microbial community composition in wild-type mice alter the intestinal IgA levels, thereby differentially influencing susceptibility to a chemically induced model of colitis (Moon et al, 2015). Likewise, it is possible that our observation of greater variation in sIgM transcript abundance in older fish, with little variation in size, is simply a reflection of increasing microbiota variation between individuals in response to widely varying microbial communities.…”
Section: Discussionmentioning
confidence: 71%
“…Our results highlight observations that some of the observed phenotypic variation in animal studies is, in part, owing to variations in the microbiota. For example, it was recently shown that differences in microbial community composition in wild-type mice alter the intestinal IgA levels, thereby differentially influencing susceptibility to a chemically induced model of colitis (Moon et al, 2015). Likewise, it is possible that our observation of greater variation in sIgM transcript abundance in older fish, with little variation in size, is simply a reflection of increasing microbiota variation between individuals in response to widely varying microbial communities.…”
Section: Discussionmentioning
confidence: 71%
“…We and others have shown that gut microbial dysbiosis contributes to susceptibility toward colitis and CAC (36)(37)(38). IgA is known to regulate the gut microbial landscape, and mice deficient in IgA and pIgR are known to harbor a dysbiotic microbiota that contributes to their increased susceptibility to colitis (33,(39)(40)(41). We therefore posited that decreased colonic IgA in Il33 -/-mice would lead them to developing a dysbiotic microbiota.…”
Section: And E) the Intestinal Iga Level In Il1amentioning
confidence: 99%
“…It is not known how TNFR2 deficiency impacts A. muciniphilia abundance, but intracellular cross-talk between short-chain fatty acid and sex-hormone signaling and gene regulation is one possibility. Sutterella, also selectively more abundant in male TNFR2 2/2 2D2 mice, has been positively correlated with autism and Down syndrome (84), as well as degradation of secretory IgA (85). In addition to providing a first line of defense against enteric toxins and pathogens, intestinal secretory IgA, promotes Ag clearance, quenches bacterial virulence factors, and changes the composition of the intestinal microbiota (86).…”
Section: Gut Microbiota In Tnfr2mentioning
confidence: 99%